Analisis Brand Experience Dan Brand Personality Terhadap Customer Loyalty Produk Indihome PT. Telkom Witel Bandung - Enur, Euis; Halim, Prihartono Aksan (Universitas Hamzanwadi, 2023)
The intention of the study was to understand the relationships between (X1:brand experience) and (Y:customer loyalty), (X2:brand personality) and (Y:customer loyalty), X1 and X2 to customer loyalty. Purposive sampling was used in addition to a sample size of around 100 responses from customers of the Indihome Wireless in Bandung, which is known as a quantitative method using a Likert scale. The information used in this study is preliminary data obtained from online questionnaires completed by respondents, as well as evaluations of validity, reliability, and hypotheses. The results of this analysis show that each individual variable and each additional variable may have a positive or significant impact on customer loyalty. In order to be able to infer that X1 (Brand Experience) and X2 (Brand Personality) are both significant, the uji T individual variable states that the sig 0,05 and Uji F state that the nilai F hitung > F tabel is 4,83.